Physicochemical characteristics of milk sold in family production units in the Atoyac River Basin in Puebla and Tlaxcala, Mexico (Agro Productividad, 2024)
Objective: To determine the physicochemical characteristics and possible adulteration of raw milk marketed in dairy family systems located in the Atoyac River Basin in Puebla-Tlaxcala.Design/methodology/approach: The physical characteristics of milk were determined: pH, acidity and freezing point; and chemical characteristics: fat, protein, lactose, minerals, non-fat solids, total solids and water content. This milk is produced and sold by 264 family production units to three cheese companies in the Atoyac River Basin in the states of Puebla and Tlaxcala. The data were analyzed by company and subsequently grouped with the Cluster technique of the SAS software.Results: Significant differences (p